Tocopherol content, weight loss and instrumental color analysis of Iberian dry-cured ham as affected by rearing and feeding systems - Beatriz Isabel; Gustavo Cordero; Clemente López-Bote; Argimiro Daza (Grasas y Aceites, 2009)
The effects of rearing (outdoor vs indoor) and feeding systems (acorn and grass vs mixed diets) on ham quality from Duroc x Iberian pigs were studied. Seven groups of 5 females each were used. One group was reared under freerange conditions and fed with acorns and grass (outdoor pigs). Six group were fed mixed diets in confinement (indoor pigs) under a factorial design 3 x 2 with three types of dietary fat: monounsaturated, polyunsaturated and medium (monounsaturated and polyunsaturated) and two levels of α-tocopheryl-acetate. The α-and γ-tocopherol contents were higher (P < 0.05) in hams from outdoor pigs than in hams from indoor pigs. The hams from indoor pigs were lighter than hams from outdoor pigs and redness values were larger in hams from outdoor pigs than in hams from indoor pigs. At 4 days of storage ham samples from outdoor pigs showed a tendency (P < 0.10) to lower weight loss than those from pigs fed a basal level of vitamin E. These results indicate that rearing outdoor and feeding Iberian pigs by acorn and grass increase the α-and γ-tocopherols and improve color and weight losses in dry-cured hams.